Pastoral care as a constant power struggle: a case study - the Garden of Hope in Taiwan - Li, Hsiu-Yu (The University of Edinburgh, 2006)
This thesis is to propose a pastoral theology through the examination of pastoral care in the social context of contemporary Taiwan. It focuses on the pastoral care provided by the Garden of Hope, an institution founded in 1988 for the rescue and rehabilitation of Taiwanese child and teenage girl prostitutes. The work of the Garden of Hope is examined from the analytical stance that recognises the impact of various issues of power in relation to the situation of girl prostitutes.

The central argument of the thesis is that issues of power are integral to the understanding of what brings young Taiwanese girls to prostitution, to their mistreatment under existing ideologies, laws and systems of control in Taiwan and even to their being cared by the pastoral care provider; and that issues of power therefore need to be constantly engaged to provide a pastoral care that will be effective to rehabilitate girl prostitutes. It is in this sense that pastoral care is defined in this thesis as "a constant power struggle ".

The research has been conducted in the field of pastoral theology, this being understood as a part of practical theology in the sense that practice precedes theory, and sociology informs theology. The research has therefore employed an empirical methodology of listening to the experience of local people - in this case the staff of the Garden of Hope, government officers, the girl prostitutes and their families - and integrating the findings of empirical research with theological and sociological theories derived from relevant literatures.

The research is contextual in that it is set in the society and culture of contemporary Taiwan. The status of women, cultural attitudes toward girl prostitutes, the subjectivity of young Taiwanese people in a time of rapid economic growth, the contextual theology of the Presbyterian Church in Taiwan (PCT), and government laws are all explored in terms of the challenges that they represent for an effective pastoral care of girl prostitutes in Taiwan.

The argument of the thesis develops through five chapters. Chapter One examines the development of pastoral care in Western society as the root of pastoral care in Taiwan as illustrated in the PCT. Chapter Two introduces sociological understandings of power, and demonstrates how these are helpful in interpreting the actual practice of social life in Taiwan and even in Biblical times. Chapters Three and Four focus on the case study of the Garden of Hope: Chapter Three discusses the problems of girl prostitution in Taiwan that the GOH has been dealing with since its creation in 1986; and Chapter Four examines the ways in which the GOH deals with issues of power related to the rehabilitation of the girl prostitutes who live in its halfway homes. Chapter Five seeks to integrate the findings of the previous chapters in a contextual understanding of pastoral care that demonstrates that power relationships are an integral part of pastoral care, and that pastoral care providers need to be able to recognise and struggle with these power issues if their care provision is to be effective.

In these terms the thesis offers an original insight into the nature and practice of pastoral care, particularly with reference to the challenges that the church in Taiwan faces in providing pastoral care for people in society at large.